More in time : a tribute to Ted Kooser - Kooser, Ted; Poli, Jessica; Abel, Marco; Schaffert, Timothy (University of Nebraska, 2021)
More in Time is a celebration and tribute to two-time United States Poet Laureate Ted Kooser.